2019
DOI: 10.3389/fphar.2019.00650
|View full text |Cite
|
Sign up to set email alerts
|

Target Identification of Active Constituents of Shen Qi Wan to Treat Kidney Yang Deficiency Using Computational Target Fishing and Network Pharmacology

Abstract: Background: Kidney yang deficiency syndrome (KYDS) is one of the most common syndromes treated with traditional Chinese medicine (TCM) among elderly patients. Shen Qi Wan (SQW) has been effectively used in treating various diseases associated with KYDS for hundreds of years. However, due to the complex composition of SQW, the mechanism of action remains unknown. Purpose: To identify the mechanism of the SQW in the treatment of KYD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 70 publications
(45 reference statements)
1
19
0
Order By: Relevance
“…This flowchart really solves the molecular mechanism of some formulas of TCM in treating complex diseases. Such as: Hua Yu Qiang Shen Tong Bi formula treats rheumatoid arthritis ( Wang et al., 2019 ), Shen Qi Wan treats kidney yang deficiency syndrome ( Zhang et al., 2019 ), and Huo Xiang Zheng Qi formula treats functional dyspepsia ( Zhao et al., 2018 ). However, there still exists some problems, such as false positive and noise in the predicted targets of components.…”
Section: Discussionmentioning
confidence: 99%
“…This flowchart really solves the molecular mechanism of some formulas of TCM in treating complex diseases. Such as: Hua Yu Qiang Shen Tong Bi formula treats rheumatoid arthritis ( Wang et al., 2019 ), Shen Qi Wan treats kidney yang deficiency syndrome ( Zhang et al., 2019 ), and Huo Xiang Zheng Qi formula treats functional dyspepsia ( Zhao et al., 2018 ). However, there still exists some problems, such as false positive and noise in the predicted targets of components.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, DHG treatment not only inhibited the fat accumulation in the liver, but also inversed the increase of body weight gain, liver index, and related adipose tissue weight in hyperlipidemic hamsters, which further confirmed that the DHG had a beneficial lipidlowering effect. Systems pharmacology has gradually become an effective method to study the active components and mechanisms of action of TCM (Zhou et al, 2019;Zhang et al, 2019). Different from most of the previous studies that usually consider ingredients from herbal databases, we take the compounds that are detected in the hamster blood as the compound source to carry out systems pharmacology research.…”
Section: Discussionmentioning
confidence: 99%
“…Applications of network pharmacology to investigate mechanism of TCM have become an indispensable method for development of TCM [7]. In many previous studies, network pharmacology has successfully predicted potential targets and pathways of TCM [8][9][10]. erefore, network pharmacology has been proved to be an effective method to explore potential targets and pathways of TCM by analyzing network of biological systems.…”
Section: Introductionmentioning
confidence: 99%